The category of health in the history of development of social and humanitarian knowledge - Shushunova, Tatyana N. (Journal of the Belarusian State University. Ecology, 2018)
The category of health in the context of socio-humanitarian knowledge is examined as one of the conditions for aneffective national strategy for sustainable social and economic development of the Republic of Belarus. The emphasisis on the philosophical aspect of the analysis of health from the sources of philosophical thought to modern concepts asa specific area of knowledge that connects the evolution of ideas about human health, their continuity, the developmentof basic ideas about its preservation.
Keywords: health; philosophy of medicine; health philosophy; physical health; spiritual health; health standards; attitudes towards health